2018
DOI: 10.3390/app8122669
|View full text |Cite
|
Sign up to set email alerts
|

Differences among Unique Nanoparticle Protein Corona Constructs: A Case Study Using Data Analytics and Multi-Variant Visualization to Describe Physicochemical Characteristics

Abstract: Gold nanoparticles (AuNPs) used in pharmaceutical treatments have been shown to effectively deliver a payload, such as an active pharmaceutical ingredient or image contrast agent, to targeted tissues in need of therapy or diagnostics while minimizing exposure, availability, and accumulation to surrounding biological compartments. Data sets collected in this field of study include some toxico- and pharmacodynamic properties (e.g., distribution and metabolism) but many studies lack information about adsorption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…159,162 Formation of protein corona has significant effect on targeting ability, cellular uptake, accumulation and toxicity of nanoparticles in living systems, 77 since the formation of protein corona has the tendency to change the biological effects of the nanoparticles. 163 The structure and composition of protein corona is largely controlled by the surface coating. 39 It was reported that protein corona formation is minimized by functionalizing agents, such as coating of AuNPs with GSH and PEG, as these reportedly shield the surface of nanoparticles from serum protein binding (opsonization).…”
Section: Interactions With Physiological Media and Biological Fluidsmentioning
confidence: 99%
“…159,162 Formation of protein corona has significant effect on targeting ability, cellular uptake, accumulation and toxicity of nanoparticles in living systems, 77 since the formation of protein corona has the tendency to change the biological effects of the nanoparticles. 163 The structure and composition of protein corona is largely controlled by the surface coating. 39 It was reported that protein corona formation is minimized by functionalizing agents, such as coating of AuNPs with GSH and PEG, as these reportedly shield the surface of nanoparticles from serum protein binding (opsonization).…”
Section: Interactions With Physiological Media and Biological Fluidsmentioning
confidence: 99%
“…After the addition of buffered AgMet dispersion in BSA solution, the dispersion underwent the peptization process, which is clearly observed in the TEM micrograph ( Figure 2 B). Additionally, Figure 2 C,D show that AgNPs are surrounded by a non-uniform BSA cloud by forming a core (AgNPs, black sphere)–shell (BSA, white-grey cloud)-type structure [ 21 , 22 ]. Undefined clouds of BSA surrounding the NPs indicate the presence of a “soft” corona [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…As another key surface property, surface charge determines the composition of protein corona that binds to the surface of NPs. For example, AuNPs with negatively charged surfaces (conjugated with a carboxyl group) formed a different protein corona than positively charged (conjugated with amine group) and neutral (conjugated with PEG) NPs . Cationic particles generally adsorb more proteins than the negative and neutral ones, mainly driven by the electrostatic interaction with the negatively charged proteins .…”
Section: Surface Properties Of Nanoparticles Determine the Formation ...mentioning
confidence: 99%